Investigating the fiscal resource curse: What's China got to do with it? - Daniel Chachu; Edward Nketiah-Amponsah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The term fiscal resource curse refers to countries' inability to raise taxes from a broad base in the presence of natural resources. We employ a novel instrumental variable strategy to estimate the causal effect of resource revenues on non-resource tax effort by exploiting the so-called 'China shock'. Since its 2001 accession to the World Trade Organization, China's non-renewable resource trade has driven up commodity prices, raising resource revenues among exporting countries. Exporting countries benefit from infrastructure projects rather than just liquid capital flows. Our results provide no consistent evidence for a fiscal resource curse. On the contrary, a onepercentage-point increase in resource revenues as a percentage of GDP leads to about a 0.3- percentage-point increase in non-resource taxes as a percentage of GDP. China's non-resource trade model might be easing binding constraints to expanding the non-resource sector and presenting an opportunity to diversify the domestic revenue base in developing countries.
Keywords: H2; H41; Q32; Q37; 330; China; infrastructure; natural resources; tax effort; trade